ANALISIS PERKEMBANGAN FARMER’S SHARE DAN MARKETING MARGIN PADI DI INDONESIA TAHUN 2010 – 2020 - Rily Yunita; Syahril Syahril; Helmi Noviar (Universitas Teuku Umar, 2021)
This study aims to determine the development of farmer's share and marketing margin of rice in Indonesia for 2010 – 2020. Farmer's share is a share of the price received by farmers with the price paid by consumers. Meanwhile, marketing margin is the difference between the price received by farmers and the price paid by consumers. This study uses secondary data obtained from government statistics and literature studies in accordance with the object of study. Farmer's share data analysis is expressed in percentages, while the marketing margin analysis is expressed in rupiah. From this study, it was found that the development of farmer's share rice for all quality groups in Indonesia in 2010 – 2020 tended to vary. Meanwhile, the development of marketing margins rice for all quality groups in Indonesia in 2010 – 2020 continued to increase from year to year although in certain years it decreased.